Electron tomography in plant cell biology. (17th November 2018) - Otegui, Marisa S; Pennington, Jannice G
Abstract : This review discusses recent advances in three-dimensional electron microscopy with an emphasis on the contributions of electron tomography to the analysis of plant organelles and cellular processes. Abstract: Electron tomography (ET) approaches are based on the imaging of a biological specimen at different tilt angles by transmission electron microscopy (TEM). ET can be applied to both plastic-embedded and frozen samples. Technological advancements in TEM, direct electron detection, automated image collection, and imaging processing algorithms allow for 2–7-nm scale axial resolution in tomographic reconstructions of cells and organelles. In this review, we discussed the application of ET in plant cell biology and new opportunities for imaging plant cells by cryo-ET and other 3D electron microscopy approaches.